Concurrent evaluation of general, immune, and genetic toxicity endpoints as part of an integrated testing strategy. (27th June 2014) - Schisler, Melissa R.; Sura, Radhakrishna; Visconti, Nicolo R.; Sosinski, Lindsay K.; Murphy, Lynea A.; LeBaron, Matthew J.; Boverhof, Darrell R.
<x xml:space="preserve">Abstract</x> Integrated testing strategies involve the assessment of multiple endpoints within a single toxicity study and represent an important approach for reducing animal use and streamlining testing. The present study evaluated the ability to combine general, immune, and genetic toxicity endpoints into a single study. Specifically, this study evaluated the impact of sheep red blood cell (SRBC) immunization, as part of the T‐cell dependent antibody response (TDAR) assay, on organ weights, micronuclei (MN) formation (bone marrow and peripheral blood), and the Comet assay response in the liver of female F344/DuCrl rats treated with cyclophosphamide (CP) a known immunosuppressive chemical and genotoxicant. For the TDAR assay, treatment with CP resulted in a dose‐dependent decrease in the antibody response with a suppression of greater than 95% at the high dose. Injection with SRBC had no impact on evaluated organ weights, histopathology, hematology, and clinical chemistry parameters. Analysis of MN formation in bone marrow and peripheral blood revealed a dose‐dependent increase in response to CP treatment. Injection with SRBC had no impact on the level of MN in control animals and did not alter the dose response of CP. There was a slight increase in liver DNA damage in response to CP as measured by the Comet assay; however, injection with SRBCs did not alter this endpoint. Overall these data provide strong support for the concurrent assessment of general, immune, and genetic toxicology endpoints within a single study as part of an integrated testing strategy approach. Environ. Mol. Mutagen. 55:530–541, 2014. © 2014 Wiley Periodicals, Inc.